2014
DOI: 10.1017/cbo9781139136358
|View full text |Cite
|
Sign up to set email alerts
|

Charity Law and the Liberal State

Abstract: Charity Law and the Liberal State considers questions relating to state action and public discourse that are raised by the law of charity. Informed by liberal philosophical commitments and of interest to both charity lawyers and political philosophers, it addresses themes and topics such as: the justifiability of the state's non-neutral promotion of charitable purposes; the role of altruism in charity law; charity law, the tax system and the demands of distributive justice; the proper treatment of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Most crucially, in light of the public perception of what it is to be charitable, they are denied the liberty to act freely in line with their consciences. While trustees are each free to express their positions and discuss matters of moral concern, it is the fulfilment of the charitable 'object(s)' or purpose(s) that is sacrosanct and prime, and charities must not act in ways that may impact negatively on their achievement (Charity Commission for England and Wales 2015a;Harding 2014;Bates Wells and Braithwaite 2008).…”
Section: Charity Law and The Exercise Of Moral Agencymentioning
confidence: 99%
See 4 more Smart Citations
“…Most crucially, in light of the public perception of what it is to be charitable, they are denied the liberty to act freely in line with their consciences. While trustees are each free to express their positions and discuss matters of moral concern, it is the fulfilment of the charitable 'object(s)' or purpose(s) that is sacrosanct and prime, and charities must not act in ways that may impact negatively on their achievement (Charity Commission for England and Wales 2015a;Harding 2014;Bates Wells and Braithwaite 2008).…”
Section: Charity Law and The Exercise Of Moral Agencymentioning
confidence: 99%
“…Turning first to charities, we have noted the growing disconnection between the concept of charity as applied in law and the public perception of what it is to be a charitable organisation on the one hand (Synge 2015;dal Pont 2014;Harding 2014;Parachin 2014), and associated lowering public trust in these organisations on the other hand (Radojev 2016a, b;Smith 2015;Charity Communications 2014). We have observed that while notions that charities are essentially of good moral standing shape public expectations of these organisations, being granted charitable status in law is not dependent upon a display of virtue (dal Pont 2014;O'Halloran 2011).…”
Section: Implications For Charities and Business Corporationsmentioning
confidence: 99%
See 3 more Smart Citations